From Product To Profit: Student Entrepreneurship Mentoring Through Production Practices and Preparation of Simple Financial Reports - Nengsi Sudirman; Arianto Dangkeng; Rafika Fausiah; Muh. Ramli; Resky Aulia Asri (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Students as aspiring entrepreneurs need to have the ability to produce products while managing business finances sustainably. However, entrepreneurship education in higher education still focuses more on production aspects than financial management. This community service activity aims to improve students' entrepreneurial competencies through mentoring in production practices and preparing simple financial reports. The method used is participatory mentoring in five stages: production practices, cost recording, simple digital bookkeeping, financial report preparation, and business profit analysis. The results show that students are able to understand the production process, identify costs, prepare digital bookkeeping, present simple financial reports, and analyze business profits. The product-to-profit approach provides a learning experience that integrates operational and financial aspects, thus supporting the development of young entrepreneurs who are able to manage their businesses professionally and sustainably.